2016
DOI: 10.1037/adb0000179
|View full text |Cite
|
Sign up to set email alerts
|

Emerging adult identity development, alcohol use, and alcohol-related problems during the transition out of college.

Abstract: Alcohol use generally peaks during the early twenties and declines with age. These declines, referred to as “maturing out,” are presumed to result from the acquisition of adult roles (e.g. marriage, employment) incompatible with alcohol use. Recent empirical evidence suggests that variables other than role transitions (e.g. personality) may also be important in understanding this process. Changes in identity that occur during emerging adulthood may also be linked to the process of maturing out of heavy drinkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 55 publications
3
20
1
Order By: Relevance
“…Additionally, mean scores on the CES-D (Audrain-McGovern et al, 2011) and GAD-7 (Bonar et al, 2018;Stein et al, 2013) were similar to other studies utilizing emerging adult samples. Total scores for the RAPI (Gates et al, 2016;Kenney et al, 2012) and RMPI (Lee et al, 2010) were also comparable to previous research.…”
Section: Preliminary Analysessupporting
confidence: 83%
“…Additionally, mean scores on the CES-D (Audrain-McGovern et al, 2011) and GAD-7 (Bonar et al, 2018;Stein et al, 2013) were similar to other studies utilizing emerging adult samples. Total scores for the RAPI (Gates et al, 2016;Kenney et al, 2012) and RMPI (Lee et al, 2010) were also comparable to previous research.…”
Section: Preliminary Analysessupporting
confidence: 83%
“…Additional analyses revealed that at 19 years, adolescents in this particular trajectory work on average more hours than adolescents in the other trajectories (mean hours stable low = 15, moderate increasing = 16, heavy increasing = 19 and peaking = 22). The responsibilities that come with the labor market entry could be the reason for the decline in drinking behavior in this group [24,57,58]. This trajectory showed no increased risk of unemployment, further supporting this notion.…”
Section: Discussionsupporting
confidence: 52%
“…In our study, the minority of adolescents in the peaking trajectory had an early onset of alcohol and cannabis use, which peaked around 16–19 years of age and declined in late adolescence and young adulthood. The majority of the adolescents had patterns of risk behaviors that remained stable tended to increase until late adolescence and young adulthood (up till 22 years; [24,39,58]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…sensation-seeking, positive and negative urgency, reward sensitivity, lack of perseverance/premeditation) and heavy drinking in emerging adults [13]. Recent longitudinal findings suggest that the influence of role transition and personality on drinking behaviour changes over the course of young adulthood, such that in early young adulthood role transitions are more influential but later personality plays a greater role [14, 15]. In addition, the expectancies an individual has for the predicted effects of alcohol may also influence how much and how often they drink.…”
Section: Introductionmentioning
confidence: 99%